2014
DOI: 10.1136/bjophthalmol-2014-305327
|View full text |Cite
|
Sign up to set email alerts
|

Multi-country real-life experience of anti-vascular endothelial growth factor therapy for wet age-related macular degeneration

Abstract: Background/aimsReal-life anti-vascular endothelial growth factor (VEGF) therapy use in patients with wet age-related macular degeneration (wAMD) was assessed in a retrospective, observational study in Canada, France, Germany, Ireland, Italy, the Netherlands, UK and Venezuela.MethodsMedical records of patients with wAMD, who started ranibizumab treatment between 1 January 2009 and 31 August 2009, were evaluated. Data were collected until the end of treatment and/or monitoring or until 31 August 2011.Results2227… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
415
3
46

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 526 publications
(493 citation statements)
references
References 18 publications
29
415
3
46
Order By: Relevance
“…Our results regarding the improvement in VA are lower compared with those reported in clinical trials (see Figure 2). Other observational studies also found lower VA improvement [10][11][12] . These differences could be due to different treatment programs and differences between the study populations.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our results regarding the improvement in VA are lower compared with those reported in clinical trials (see Figure 2). Other observational studies also found lower VA improvement [10][11][12] . These differences could be due to different treatment programs and differences between the study populations.…”
Section: Discussionmentioning
confidence: 85%
“…AURA was an observational multi-country study including 2 227 patients treated with ranibizumab in standard clinical practice 11 . The authors found that the number of injections given in clinical practice is less than in clinical trials (mean injections at 1 year = 5 and at 2 years = 2.2) and that the mean change in VA was + 2.4 and + 0.6 letters at 1 and 2 years respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] These poor visual outcomes may stem from an inability to adhere to strict a PRN regimen (which is required for PRN to be effective) in routine clinical practice; this hypothesis is supported by the low injection frequency reported by these studies (a mean number of 4.3-5.1 injections over 12 months). 17,[19][20][21] To better understand the overall picture concerning the real-world effectiveness of ranibizumab, a review of the literature was conducted to identify studies of ranibizumab in clinical practice. This review provides both a summary of the design and methodological quality of the studies and a basic analysis of VA outcomes from the studies.…”
Section: Introductionmentioning
confidence: 53%
“…Upon screening using our pre-defined inclusion criteria, 143 were discarded after review of the publication titles, 27 were discarded after the review of publication abstracts, and a further 8 were discarded after the review of full text. No additional studies were identified through the review of reference lists within the publications we identified; however, we were aware of an important study (AURA) 20 that was not identified by the pre-defined search terms but was relevant to this review. Therefore, 20 studies in total were included in our evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation